Retrieval of soil moisture based on Gaofen-3 (GF-3) satellite synthetic aperture radar data over agricultural fields - ZHANG Linlin; LEI Zhibin; WANG Liping; MENG Qingyan; ZENG Jiangyuan (浙江大学学报. 农业与生命科学版, 2024)
Soil moisture is the basic condition for crop growth. A new retrieval algorithm for soil moisture was proposed based on C-band synthetic aperture radar (SAR) data from Gaofen-3 (GF-3) satellite, and soil moisture of agricultural fields with a regional scale spatial resolution of 8 m was obtained. First, the algorithm selected the optical vegetation water index based on PROSAIL model, measured vegetation canopy water content and Landsat-8 optical data. The parameters of water cloud model were calculated，and soil direct backscattering coefficients were obtained. Second, the radar backscattering influence mechanism was simulated using an advanced integral equation model (AIEM), and the combined roughness of soil surface was calculated based on the characteristics of radar data at high and low incidence angles. Finally, soil moisture was retrieved using co-polarization radar data from GF-3 satellite over agricultural fields, and this was verified with measured data. The results showed that there was a high consistency between the measured soil moisture and estimated soil moisture, and vertical-vertical (VV) polarization exhibited higher retrieval accuracy, with a determination coefficient of 0.595 6 and a root mean square error of 0.041 5 m3/m3. The results can provide algorithmic references for the GF-3 satellite to obtain high-resolution soil moisture information.